Assessment of the Needs of Caregivers of Stroke Patients at State-Owned Acute-Care Hospitals in Southern Vietnam, 2011 - Yumiko Hayashi, MS, MBA; Hoang Hoa Hai, MD; Nguyen Anh Tai, MD (Centers for Disease Control and Prevention, 2013)
Introduction Care for stroke patients has improved steadily in southern Vietnam. Medical treatments such as thrombolytic therapy have been implemented at several hospitals, and stroke-care units composed of a team of various health professionals have been created. However, little attention has been focused on providing support to caregivers of stroke patients. This study aimed to characterize the caregivers of stroke patients who were treated in state-owned acute-care hospitals and to learn about their needs when patients are discharged. Such information can be used to enhance the caregiver's support system. Methods We used questionnaires to conduct a descriptive study in 2011 at a state-owned acute-care hospital in southern Vietnam. We recruited study participants from among caregivers of stroke patients who had been informed of their hospital discharge date. We assessed 8 caregiver characteristics, and caregiver participants selected their needs from the survey's list of 15 possible needs. We analyzed the data by using the independent sample t test and logistic regression. Results Of the 93 caregivers who consented to participate, 86 (92.5%) completed the survey and indicated their concerns at discharge. The most frequently cited need was information on how to prevent stroke recurrence (72, 83.7%), followed by which drugs are most effective in preventing a relapse (62, 72.1%), how long recovery would take (61, 70.9%), and availability of hospitals in the patient's hometown (60, 69.8%). A little over half of caregivers indicated financial concerns. A caregiver's need for information on diet for a stroke survivor increased with the caregiver's education level. Conclusions This study revealed several needs among caregivers of stroke survivors in southern Vietnam that are similar to those found by studies of caregivers of stroke survivors in high-income countries. Our findings suggest that comprehensive stroke care that includes caregiver education about healthful diets and prevention of stroke recurrence is needed at state-owned acute-care hospitals in southern Vietnam.